Communication systems and information technology selected papers from the 2011 International Conference on Electric and Electronics (EEIC 2011) in Nanchang, China on June 20-22, 2011, volume 4 - International Conference on Electric and Electronics (2011 Nanchang, China); Ma, Ming.; SpringerLink (Online service). (Berlin Springer, 2011)
This volume includes extended and revised versions of a set of selected papers from the International Conference on Electric and Electronics (EEIC 2011) , held on June 20-22 , 2011, which is jointly organized by Nanchang University, Springer, and IEEE IAS Nanchang Chapter.   The objective of EEIC 2011 Volume 4 is to provide a major interdisciplinary forum for the presentation of new approaches from Communication Systems and Information Technology, to foster integration of the latest developments in scientific research. 137 related topic papers were selected into this volume. All the papers were reviewed by 2 program committee members and selected by the volume editor Prof. Ming Ma.   We hope every participant can have a good opportunity to exchange their research ideas and results and to discuss the state of the art in the areas of the Communication Systems and Information Technology.
From the content: The Design and Implementation of DDR PHY Static Low-power Optimization Strategies -- Design on Triple Bi-directional DC/DC Converter Used for Power Flow Control of Energy Storage in Wind Power System -- ESL Based SoC System Bandwidth Estimation Method -- Cellular Automaton for Super-paramagnetic Clustering of Data -- Embedded Memory Wrapper Based on IEEE 1500 Standard -- A SVPWM Control Strategy for Neutral Point Potential Compensation in Three-level Inverter -- Process Mining: A Block-Structured Mining Approach.
Electronic reproduction.
Keywords: Computer engineering -- Congresses; Electronics -- Congresses; Engineering -- Congresses; Electronic books